Escuela de literatura i filosofía. program for the superior class of english (2009)
I.- General Observations. II.- Of nouns. III.- Person. IV.- Gender. V.- Number. VI.- Case. VII.- Of articles. VIII.- Of adjetives. IX.- Of pronouns. X.- Compound personal pronouns. XI.- Of adjetive pronouns. XII.- Of tense. XIII.- Of relative pronouns. XIV.- Of conpoud and interrogative pronouns. XV.- Of the verb. XVI.- Mood or mode. XVII.- Of participles. XVIII.- Formation of the passive verb. XIX.- Of the auxiliary verb. XX.- Signs of the moods. XXI.- Sings of the tenses of the indicative. XXII.- Conjugation of verbs. XXIII.- Of irregular verbs. XXIV.- Government of the infinitive. XXV.- Participial adjectives. XXVI.- Of the auxiliary verbs. XXVII.- Of defective verbs. XXVIII.- Of adverbs. XXIX.- Of prepositions. XXX.- Of conjunctions. XXXI.- Of interjections. XXXII.- Of the agreement or nouns. XXXIII.- Of nouns used independently. XXXIV.- Of nouns in the case absolute. XXXV.- Of the infinitive mood. XXXVI.- Agreement of nouns and pronouns with verbs and amp;.a. XXXVII.- Of negative and afirmative sentences. XXXVIII.- Government of the two objective cases after some verbs. XXXIX.- Violation of the natural construction of the passive voice. XL.- Of words used as different parts of apeech. XLI.- Contractions. XLII.- Inverted sentences. XLIII.- Prosody.- XLIV.- Puntuation.